Requirement for phosphorylation of P53 at Ser312 in suppression of chemical carcinogenesis - Slee, E; Lu, X (Springer Nature, 2013)
The p53 tumour suppressor is activated in response to a wide variety of genotoxic stresses, frequently via post-translational modification. Using a knock in mouse model with a Ser312 to Ala mutation, we show here that phosphorylation of p53 on Ser312 helps to prevent tumour induction by the alkylating agent MNU, which predominantly caused T cell lymphomas. This is consistent with our previous observation that p53312A/A mice are more susceptible to X-ray induced tumourigenesis. Phosphorylation on Ser312 aids p53's interaction with E2F1 and enhances p53-mediated apoptosis. Loss of E2F1 alone does not affect tumour susceptibility to MNU, but its absence partially rescues tumour formation in p53312A/A mice, thus reflecting the oncogenic properties of E2F1. Our data confirms the participation of Ser312 phosphorylation in tumour suppression by p53.